The experience of agency in human-computer interactions: a review - Limerick, Hannah; Coyle, David; Moore, James W. (Frontiers in Human Neuroscience, 2014)
The sense of agency is the experience of controlling both one’s body and the external environment. Although the sense of agency has been studied extensively, there is a paucity of studies in applied ‘real-life’ situations. One applied domain that seems highly relevant is human-computer-interaction (HCI), as an increasing number of our everyday agentive interactions involve technology. Indeed, HCI has long recognized the feeling of control as a key factor in how people experience interactions with technology. The aim of this review is to summarize and examine the possible links between sense of agency and understanding control in HCI. We explore the overlap between HCI and sense of agency for computer input modalities and system feedback, computer assistance, and joint actions between humans and computers. An overarching consideration is how agency research can inform HCI and vice versa. Finally, we discuss the potential ethical implications of personal responsibility in an ever-increasing society of technology users and intelligent machine interfaces.